2011
DOI: 10.1002/acr.20612
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hand bone mineral density and the association with the level of disease activity in patients with rheumatoid arthritis: Bone mineral density measurements in a multicenter randomized clinical trial

Abstract: Objective. To determine if metacarpal bone mineral density (mBMD) gain occurs in patients with rheumatoid arthritis (RA). If mBMD loss is driven by inflammation, we expect to find mBMD gain in patients who are in remission. Methods. mBMD was measured by digital x-ray radiogrammetry in consecutive radiographs of 145 patients with RA with either continuous high disease activity (HDA; Disease Activity Score [DAS] >2.4), low disease activity (LDA; 1.6 > DAS < 2.4), or continuous clinical remission (CR; DAS <1.6) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
1
11
0
3
Order By: Relevance
“…RA is associated with periarticular osteopenia, systemic osteoporosis, and bone erosion, which increase in severity as the disease progresses . In our study, microCT analysis revealed that HFD exacerbates the severity of bone loss induced by experimental arthritis.…”
Section: Discussionsupporting
confidence: 50%
“…RA is associated with periarticular osteopenia, systemic osteoporosis, and bone erosion, which increase in severity as the disease progresses . In our study, microCT analysis revealed that HFD exacerbates the severity of bone loss induced by experimental arthritis.…”
Section: Discussionsupporting
confidence: 50%
“…A large randomized clinical trial [51], in which the differences on bone loss between traditional disease-modifying antirheumatic drugs and various anti-TNF α regimens were evaluated, showed that conventional treatment alone was associated with a greater hand bone loss compared to the association with anti-TNF α therapy; however, these effects disappeared when results were adjusted for disease activity. Further, a post hoc analysis grouping patients by therapeutic response showed that the protective effect on bone was associated with clinical remission, irrespective of treatment with anti-TNF α [52]. Conversely, a second well-powered randomized clinical trial showed that the anti-TNF α Adalimumab in combination with Methotrexate reduced hand bone loss independently of clinically assessed disease activity and inflammatory status [53], suggesting that the beneficial effects of anti-TNF α therapy could not be limited to the control of inflammation, but also to its ability to inhibit the direct effect of TNF α on osteoclast activation by binding to TNF α receptor placed on osteoclast precursors.…”
Section: Treatment Of Ra With Biologic Drugs and Bone Lossmentioning
confidence: 99%
“…Only radiographic disease progression, post-menopausal status, and inflammation were associated with hand bone loss after adjustment for various covariates [81]. A post-hoc analysis of the data grouping patients by therapeutic response instead of treatment regimen, found that gain in metacarpal bone occurred in association with clinical remission, regardless of the previous or current use of anti-TNF therapy [82••], supporting the hypothesis that anti-TNF therapy decreases bone loss through tight control of disease activity.…”
Section: Anti-tnf Agents and Bone Loss In Patients With Rheumatoid Armentioning
confidence: 99%